Gradiente de mudança na cobertura vegetal numa fina escala espacial e os seus efeitos sobre a diversidade de borboletas frugívoras (Nymphalidae) - Silva, Gabriela de Araujo (2023)
Tropical dry forests (TDFs) have undergone modifications caused by human action, which harm and biological conservation, and although there are many studies on the structure of the butterfly community in humid forests, in TDFs information is still scarce. Thisstudy analyzed the spatial variation of the fruit-feeding butterflies community in environmental gradients (forest interior, abrupt transition and pasture) located in three mountains belonging to the “Serra da Jacobina” complex, Bahia, Brazil, in different seasons. Butterfly collections were carried out with 117 baited traps, organized in nine transects of 13 traps each, per collection season. 1092 individuals belonging to 36 species of the Nymphalidae family were sampled. The composition of butterflies did not differ between environments (forest and pasture) and seasons. Forests had the greatest abundance and richness of butterflies, and tree density was a crucial factor in this result. Butterfly species richness was highest during the rainy season, and abundance did not differ between seasons. The environmental gradient affected species richness during the dry season, but did not influence butterfly abundance in any season. Hamadryas februa proved to be an excellent indicator species for conserved habitats in the Caatinga. The modification of habitats and resources, tree density and seasons are important factors in explaining the structure of fruit-feeding butterflies in the Caatinga. Rotating pastures and maintaining native and fruit trees, even in pastures, can help maintain the diversity and ecosystem services provided by insects, including fruit-feeding butterflies.